Targeting of a Helix‐Loop‐Helix Transcriptional Regulator by a Short Helical Peptide. (5th September 2017) - Roschger, Cornelia; Neukirchen, Saskia; Elsässer, Brigitta; Schubert, Mario; Maeding, Nicole; Verwanger, Thomas; Krammer, Barbara; Cabrele, Chiara
Abstract: The Id proteins (Id1–4) are cell‐cycle regulators that play a key role during development, in cancer and vascular disorders. They contain a conserved helix‐loop‐helix (HLH) domain that folds into a parallel four‐helix bundle upon self‐ or hetero‐association with basic‐HLH transcription factors. By using such protein–protein interactions, the Id proteins inhibit cell differentiation and promote cell‐cycle progression. Accordingly, their supporting role in cancer has been convincingly demonstrated, which makes these proteins interesting therapeutic targets. Herein we present a short peptide containing an (i, i+4)‐lactam bridge and a hydrophobic (Φ) three‐residue motif Φ(i)−Φ(i+3)−Φ(i+6), which adopts a helical conformation in water, shows Id protein binding in the low‐micromolar range, penetrates into breast (MCF‐7 and T47D) and bladder (T24) cancer cells, accumulates in the nucleus, and decreases cell viability to ∼50 %. Thus, this cyclopeptide is a promising scaffold for the development of Id protein binders that impair cancer cell viability. Abstract : Make the right arrangement : A lactam‐bridge‐constrained nonapeptide displaying a hydrophobic (Φ) three‐residue motif Φ(i)−Φ(i+3)−Φ(i+6) can mimic a helical portion of the dimerization domain of the Id protein, penetrate cancer cells, accumulate in the nucleus, and impair cell growth and viability.